Oral diclofenac potassium versus hyoscine-N-butyl bromide for pain relief during copper intrauterine device insertion: randomized clinical trial - Abbas, Ahmed M.; Abdel-Ghany, Mohammed F.; Mohammed, Nadia Abdullah; Khodry, Mostafa; Michael, Armia; Abdelfatah, Laila E.; Ramadan, Hosam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Present study was carried out to compare the analgesic effect of oral diclofenac potassium versus hyoscine-N-butyl bromide (HBB) for pain relief during copper intrauterine device (IUD) insertion. Methods: It was a a randomized clinical trial carried out at Assiut University Hospital, Assiut, Egypt. Parous women eligible for Copper IUD insertion were recruited and randomized in a 1:1 ratio to diclofenac potassium or HBB. The participants were asked to take 2 tablets of the study medications 30 minutes before IUD insertion. The primary outcome was the participant's self-rated pain perception using a 10-cm Visual Analogue Scale (VAS) during IUD insertion. We considered a 1.5 cm difference in VAS scores between study groups as clinically significant. Results: One hundred eight women were enrolled (n=54 in each group). Diclofenac significantly has lower mean pain score during speculum placement (1.73 vs. 2.13) and tenaculum placement (1.85 vs. 2.3) than HBB with p<0.001. No statistical significant differences between both groups in other steps of IUD insertion. Additionally, the duration of IUD insertion was significantly lower in the diclofenac group (5.34±0.76 vs. 5.74±1.23 minutes, p=0.045). No women reported side effects in both groups. Conclusions: The use of oral diclofenac potassium 30 minutes prior to copper IUD insertion slightly reduce the insertional pain and duration than oral HBB with no adverse effects.